Interregionalism and international relations - Hänggi, Heiner; Roloff, Ralf, 1964-; Rüland, Jürgen, 1953- (Routledge advances in international relations and global politics ;, 2006)
This volume presents the state of the art of the new phenomenon interregionalism examining both empirical observations and theoretical explanations.